2022
DOI: 10.3390/ijms23126420
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biological Features of Wild European Rabbit Mesenchymal Stem Cells Derived from Different Tissues

Abstract: Although the European rabbit is an “endangered” species and a notorious biological model, the analysis and comparative characterization of new tissue sources of rabbit mesenchymal stem cells (rMSCs) have not been well addressed. Here, we report for the first time the isolation and characterization of rMSCs derived from an animal belonging to a natural rabbit population within the native region of the species. New rMSC lines were isolated from different tissues: oral mucosa (rOM-MSC), dermal skin (rDS-MSC), sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 60 publications
2
12
1
Order By: Relevance
“…Passaged cells had a more uniform morphology and developed into colonies as the culture developed. These morphological observations suggest that the isolated cells may contain both mature and progenitor populations, in line with what we have demonstrated in earlier studies on porcine, bovine, and rabbit species [29][30][31][32]. Our results show that all emMSCs isolated were positive for CD9, CD29, CD90, and CD44 characteristic mesenchymal markers not previously reported in European mink.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Passaged cells had a more uniform morphology and developed into colonies as the culture developed. These morphological observations suggest that the isolated cells may contain both mature and progenitor populations, in line with what we have demonstrated in earlier studies on porcine, bovine, and rabbit species [29][30][31][32]. Our results show that all emMSCs isolated were positive for CD9, CD29, CD90, and CD44 characteristic mesenchymal markers not previously reported in European mink.…”
Section: Discussionsupporting
confidence: 92%
“…POU5F1, naturally expressed in embryonic and adult stem cells, has been identified as a key regulator of pluripotent stem cell differentiation and self-renewal [34]. Recent studies have reported the detection of POU5F1 or its transcription factor OCT4 in porcine [32], bovine [29,31], or wild European rabbit MSCs [30]. Although the MSC marker STRO1 has been reported in Ferret Dental Pulp Stem Cells, we were not able to detect its expression in none of the here characterized emMSCs.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations